2019
DOI: 10.1186/s12989-019-0305-5
|View full text |Cite
|
Sign up to set email alerts
|

Airport emission particles: exposure characterization and toxicity following intratracheal instillation in mice

Abstract: Background Little is known about the exposure levels and adverse health effects of occupational exposure to airplane emissions. Diesel exhaust particles are classified as carcinogenic to humans and jet engines produce potentially similar soot particles. Here, we evaluated the potential occupational exposure risk by analyzing particles from a non-commercial airfield and from the apron of a commercial airport. Toxicity of the collected particles was evaluated alongside NIST standard reference diesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 64 publications
2
63
1
Order By: Relevance
“…Carbon black nanoparticles did not induce DNA strand breaks in the current study, but we have previously found CB-induced DNA strand breaks in BAL, lung and liver following inhalation and instillation [5,22,36,44,62,74,75]. We used 0.1%tween as vehicle, since not all the DEPs could be dispersed satisfactory in pure water or 2% serum, which are the preferred vehicles [12,40,41,42,43,44,45]. We have previously compared the effect of vehicle on CB-, TiO 2 -and CNT-induced toxicity [35].…”
Section: Dna Damage and Ros Generationmentioning
confidence: 75%
See 4 more Smart Citations
“…Carbon black nanoparticles did not induce DNA strand breaks in the current study, but we have previously found CB-induced DNA strand breaks in BAL, lung and liver following inhalation and instillation [5,22,36,44,62,74,75]. We used 0.1%tween as vehicle, since not all the DEPs could be dispersed satisfactory in pure water or 2% serum, which are the preferred vehicles [12,40,41,42,43,44,45]. We have previously compared the effect of vehicle on CB-, TiO 2 -and CNT-induced toxicity [35].…”
Section: Dna Damage and Ros Generationmentioning
confidence: 75%
“…This could be due to the low level of inflammation caused by the relatively low dose levels used in the current study. The standard diesel exhaust particles NIST2975 and NIST1650b did not induce neutrophil influx at 54 ug/mouse 28 days post-exposure in similar experimental set-ups [12,62].…”
Section: Inflammation and Acute Phase Responsementioning
confidence: 76%
See 3 more Smart Citations